Analisa Kesalahan Ejaan Berbahasa Dalam Skripsi Mahasiswa PGMI STAI Barumun Raya Sibuhuan - Robiatul Adawiyah Sir; Lina Mayasari Siregar; Rizki Hamdan (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2023)
The problem in this research is that there are still students who still make mistakes in writing their thesis and also in using punctuation marks and the solution that the researcher provides is to upload the file to Google Drive and carry out analysis using Google Doc. The objectives of this research are (1) To find out language spelling errors in preparing thesis proposals for PGMI STAIBR Sibuhuan students. (2) To find out writing errors in STAIBR Sibuhuan student theses. (3) To describe spelling errors in using capital letters, errors in using italics, and errors in using bold letters in PGMI STAIBR Sibuhuan student theses. In this research the author used a type of field research, the design used was qualitative research, namely research that produces data in the form of written or spoken words from the people being observed. The researcher checked the validity of the data by means of source triangulation and technical triangulation. Source triangulation is triangulation carried out by interviewing various sources, such as the head of the library and lecturers, students from the class of 2017. However, the results obtained must remain the same. Meanwhile, technical triangulation is triangulation carried out by researchers by collecting different data from the same source. By using triangulation techniques in data collection, the data obtained will be better and more certain. Analysis of capital letter errors in writing and italics in students' theses at the Madrasah Ibtidaiyah Teacher Education Study Program (PGMI) Barumun Raya Islamic College (STAIBR) Sibuhuan. caused by errors in the use of capital letters as elements of the first letter of a word at the beginning of a sentence, the first letter of the name of a nation, ethnic group, and language. Analysis of errors in writing prepositions in, to and from students' theses at the Islamic High School Teacher Education Study Program (PGMI). Islam Barumun Raya (STAIBR) Sibuhuan is due to ignorance that the writing must be written separately from the words of its followers or a combination of words that are commonly considered as one word. Analysis of errors in the use of punctuation marks in students' theses at the Madrasah Ibtidaiyah Teacher Education Study Program (PGMI) Barumun Islamic College Raya (STAIBR) Sibuhuan errors which include errors in the use of the period punctuation mark (.), errors in the use of the comma punctuation mark (,), errors in the use of the colon (:), and errors in the use of the question mark (?) errors. Punctuation errors are caused by differences in perception in the use of punctuation marks in accordance with EYD guidelines.